FINANCIAL PERFORMANCE EVALUATION OF INDIAN CHEMICAL COMPANIES WITH REFERENCE TO EVA AND MVA - Moholkar, Nilambari; Choudhari, Amey Adinath (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With an increasingly competitive and capital-intensive industrial environment, the importance of measuring financial performance using value-based metrics is steadily gaining momentum. The present study intends to evaluate the financial performance of select Indian chemical companies from the perspective of management by Economic Value Added (EVA) and Market Value Added (MVA). Unlike traditional accounting measures, EVA and MVA measure the concepts of economic profit and market value, respectively, thereby giving managers insights into whether and how they are creating value for shareholders. This study is focused on understanding to what extent these metrics are perceived and applied by managers in making strategic decisions within the chemical industry. A quantitative research design involving the use of a questionnaire was chosen, which purposively sampled 40 managerial-level respondents from within five Indian chemical companies. Collected data were analyzed using regression analysis and ANOVA with SPSS and are graded on a 5-point Likert scale. Analysis of the collected data showed strong statistical significance in relationships between managers' perceptions of EVA/ MVA and their perception of overall performance of the company. It also established that demographic and professional variables, particularly experience, department, and designation, impose significant influences on perception. Findings indicate that more experienced, senior, and finance-background managers tend to be more aware of and thus utilize EVA/MVA in performance evaluations. From this study, it emerged that EVA and MVA are perceived by a large number of managers in the chemical industry as relevant and useful. It has been recommended that EVA/MVA training be provided to all managerial layers and that EVA/MVA be incorporated into performance appraisal systems to further advance strategic financial planning in the long run. The study, therefore, contributes to academia and the real world by emphasizing the urgent need for valuing-based performance evaluation in the Indian industry.